Kesulitan Siswa Kelas VII SMP dalam Berpikir Kritis Matematis Pada Materi Garis dan Sudut - Zahra, Fatikhah Az; Hakim, Dori Lukman (Universitas Batanghari Jambi, 2022)
This study aims to describe the difficulties of seventh grade students in junior high school in mathematical critical thinking when solving line and angle problems. The subjects used in this study were 28 students of class VII.2 in one of the junior high schools in Bekasi City. To measure students' critical thinking skills, researchers used a description test instrument as many as 4 questions. This article is studied descriptively with a qualitative method. Aspects of critical thinking skills are measured based on how students are able to (1) interpret conjectures (2) evaluate, (3) solve problems, and (4) conclude. Technical data analysis includes data collection, data presentation, data reduction, and drawing conclusions. The calculation results show that students' critical thinking skills on the interpretation indicator get a percentage of 70.54% in the good category, the analysis gets a percentage of 68.75% in the good category, the evaluation gets a percentage of 26.48% with the less category, and inference gets a percentage of 40.48 % with sufficient category. These results show that the factors causing the difficulty experienced are thought to be because students do not understand simple concepts, are unable to translate questions into mathematical sentences, do not know the meaning of the problems presented as work steps.